2009
DOI: 10.5194/bgd-6-1875-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calcification of the cold-water coral <i>Lophelia pertusa</i> under ambient and reduced pH

Abstract: Abstract. The cold-water coral Lophelia pertusa is one of the few species able to build reef-like structures and a 3-dimensional coral framework in the deep oceans. Furthermore, deep cold-water coral bioherms are likely among the first marine ecosystems to be affected by ocean acidification. Colonies of L. pertusa were collected during a cruise in 2006 to cold-water coral bioherms of the Mingulay reef complex (Hebrides, North Atlantic). Calcium-45 labelling was conducted shortly after sample collection onboard… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 40 publications
7
35
1
Order By: Relevance
“…This change can have a profound impact on calcifying fauna. Aragonite, high magnesium calcite and calcite are the main calcium carbonate crystals made by these organisms and, because high magnesium calcite and aragonite are more soluble than calcite, the species that use these compounds – such as scleractinian corals and echinoderms – are more vulnerable and will be the first to be affected [233][236]. Deep-water corals are one of the most important taxa to be affected, both because of their contribution to deep-water diversity and because of their structural role in providing habitat to a variety of other species [237].…”
Section: Resultsmentioning
confidence: 99%
“…This change can have a profound impact on calcifying fauna. Aragonite, high magnesium calcite and calcite are the main calcium carbonate crystals made by these organisms and, because high magnesium calcite and aragonite are more soluble than calcite, the species that use these compounds – such as scleractinian corals and echinoderms – are more vulnerable and will be the first to be affected [233][236]. Deep-water corals are one of the most important taxa to be affected, both because of their contribution to deep-water diversity and because of their structural role in providing habitat to a variety of other species [237].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this high variation in coral-associated assemblages may reflect local, inter-colony differences in host status, such as genetic identity [45], physiological condition [46], or developmental state ([47] and references therein). In their study of M. oculata -associated microbes, Hansson et al [29] also reported significant inter-colony differences, which may even be further enhanced by intra-colony differences between single polyps [48], [49]. In addition to passive controls, bacterial colonization may also be actively regulated by the coral host (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…So far only three experimental studies on the effects of ocean acidification have been published. The rate of net calcification of Lophelia pertusa from Norwegian waters was shown to decline under future pCO 2 conditions [19], [20], while no or even a positive long-term (6 months) response of net calcification was observed [20]. A third study investigated the short-term response of net calcification of the Mediterranean coral Madrepora oculata under pCO 2 values reflecting past, pre-industrial and future conditions.…”
Section: Introductionmentioning
confidence: 99%
“…More than 70% of cold-water coral communities are found in regions that will be undersaturated with respect to aragonite by the end of the century [23]. However, experimental as well as observational evidence has shown that some cold-water corals are able to cope and maintain positive skeletal growth even in waters undersaturated in Ω a [19], [20], [24]. Furthermore, the study of Form & Riebesell [20] found a decline of net calcification at elevated pCO 2 in a short-term experiment and a stimulating effect in a long-term experiment from which they concluded that the cold-water coral L. pertusa is able to acclimate to higher pCO 2 .…”
Section: Introductionmentioning
confidence: 99%